PENGARUH MODEL GROUP INVESTIGATION DAN MODEL GROUP INVESTIGATION DENGAN AfL TERHADAP HASIL BELAJAR MATEMATIKA - Nunung Sobarningsih; Tika Karlina Rachmawati (Universitas Sultan Ageng Tirtayasa, 2018)
The purpose of this study was to find out which results in learning outcomes better in math between the model of Group InvestigationGroup Investigation model with Assessment for Learning(AfL), or direct learning model in the subject of Kapita Selekta Matematika SD. Research methodology in this research was quasi experimental research.Population in this research was all students of Mathematics Education of Faculty of Tarbiyah and Teacher of UIN Sunan Gunung Djati Bandung Academic Year 2016/2017. While the samples of this study were students of Mathematics Education in first semester consisting of 3 classes with total respondents 117 students. The data collection used the test method in the form of multiple choices of 20 items. Prerequisite test included normality test population using method ofLilliefors and homogeneity of the population variance using Bartlett method.With α = 0.05, it can be concluded that the sample was from a normally distributed population and has the same variance.Analysis of data using one way analysis of variance with different cells, followed by a multiple comparison test using Scheffe method.Based on the results, it can be concluded that the model group investigation with the AfL results mathematics learningbetter than the model group investigation, a model group investigation with the AFL yield better mathematics learning than direct instructional model, and the model group investigation yield mathematics learning better than the direct learning model. Keywords: Group Investigation, Assessment For Learning, Learning Model, Learning Outcomes